2007
DOI: 10.1007/s10822-007-9147-6
|View full text |Cite
|
Sign up to set email alerts
|

Computational study on mechanism of G-quartet oligonucleotide T40214 selectively targeting Stat3

Abstract: The mounting evidences have shown that signal transducer and activator of transcription 3 (Stat3) is a critical target for cancer therapy. Recently, we developed a G-quartet oligonucleotide T40214 as a novel and potent Stat3 inhibitor. T40214 specifically inhibited DNA-binding activity of Stat3 and significantly suppressed the growth of many tumor xenografts in nude mice. To determine the mechanism of GQ-ODNs selectively targeting Stat3, we established a 3D model of complex T40214/p-Stat3 dimer based on experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 41 publications
(48 reference statements)
1
18
0
Order By: Relevance
“…To validate data generated with STA21, we also tested the oligonucleotide G-quartet T40214, a different class of STAT3 inhibitor that specifically blocked phosphorylation-dependent STAT3 dimerization 17;18 . Compared to those treated with a scrambled control oligonucleotide, T40214 significantly reduced the aggregation of human platelets induced by 5 μg/ml, but not 10 μg/ml of collagen (Figure 2A & 2B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To validate data generated with STA21, we also tested the oligonucleotide G-quartet T40214, a different class of STAT3 inhibitor that specifically blocked phosphorylation-dependent STAT3 dimerization 17;18 . Compared to those treated with a scrambled control oligonucleotide, T40214 significantly reduced the aggregation of human platelets induced by 5 μg/ml, but not 10 μg/ml of collagen (Figure 2A & 2B).…”
Section: Resultsmentioning
confidence: 99%
“…It is in a linear structure in low extracellular [K + ] (~5 mM), but forms a symmetrical G-quartet structure in high intracellular [K + ] (~140 mM) when it is delivered into cells using polyethyleneamine nanobeads (PEI, MW ~25,000, Aldrich Chemical, WI) as a carrier 17 . It binds the SH2 domain of STAT3 to inhibit the tyrosine phosphorylation and dimerization of STAT3 18;19 . T40214 and a scrambled control oligonucleotide (CGGGGCGGGGCGGGGC) were commercially synthesized (Midland Certified Reagent Co., Midland, TX) and purified by anion exchange high pressure liquid chromatography on Q Sepharose followed by pressure filtration in H 2 O.…”
Section: Methodsmentioning
confidence: 99%
“…The reduced expression of these gene products inhibits proliferation and increases apoptosis in a variety of tumor cell lines [194,195] and induces tumor regression in xenograft models [196,197]. The G-quartet ODN, which forms four-stranded G-quartet structures [154], uses another mechanism: it disrupts STAT3:STAT3 dimers and inhibits STAT3 binding to DNA [155], thereby inducing tumor cell apoptosis and tumor regression [156,157,193]. Another effective method of blocking STAT3 activity with ODNs is the use of siRNA to degrade STAT3 mRNA.…”
Section: Stat3 Inhibitors As Potential Cancer Preventive Agentsmentioning
confidence: 99%
“…They promoted apoptosis and reduced angiogenesis and cell proliferation. Computer-assisted docking analysis revealed that the oligonucleotide is likely folded into a G-4 structure and interacts with the SH2 domains of Stat3 homodimers thereby destabilizing dimer formation and reducing DNA-binding activity [54]. Moreover, it forms Hbonds with residues Q643, Q644, N646, and N647, which are critical for the binding interaction.…”
Section: Stat3 -Directed Aptamersmentioning
confidence: 99%